Features of the arterial hypertension clinical course in patients with ischemic heart disease and atrial fibrillation. - M. I. Yalovenko; O. O. Khaniukov (Medičnì Perspektivi)
More than 30% of the world's population suffer from arterial hypertension (AH). AH is one of the important cardiovascular risk factors. AH is associated with a 1.5-fold increase in the risk of atrial fibrillation (AF). AF is the most common cardiac arrhythmias in the population. Nowadays, AF is regarded as potentially lethal arrhythmia, in consideration of the broad range of its negative consequences not only due to significant deterioration in the quality of the patients’ life but also due to related significant increase in the incidence of serious complications and death. Objective: to study the features of the AH clinical course, the nature of the target organs lesion in patients with ischemic heart disease with and without permanent form of atrial fibrillation. The study included 78 patients, average age was 66,3±1,0, men – 43 (55,1%). Patients were divided into 2 groups: group 1 (n=42) consisted of patients with AH, IHD and permanent AF; group 2 (n=36) included patients with AH and IHD without heart rhythm disturbances. The analysis of the frequency of lesions of target organs in groups 1 and 2 showed that the III degree of hypertension was detected in 25 (59,5%) patients in group 1 and in 8 (22,2%) patients in group 2. Degree III was diagnosed in 17 (40,5%) and 24 (66,6%) patients of 1-st and 2-nd groups, respectively. Absence of targets organ damage in group 2 was documented in 4 (11,1%) patients. AF presence is associated with a severe course of hypertension and more frequent lesion of target organs. Based on the research results, it was established a direct relation between the duration of AH and the duration of the permanent form of AF. It is expedient for patients with AF arisen against the background of AH to achieve target levels of BP for prevention disease progression and improving the prognosis.